2012
DOI: 10.1016/j.mayocp.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Emergency Response Team Activation at a Large Tertiary Medical Center

Abstract: Objective: To study characteristics and outcomes associated with emergency response team (ERT) activation in postsurgical patients discharged to regular wards after anesthesia. Patients and Methods:We identified all ERT activations that occurred within 48 hours after surgery from June 1, 2008, through December 31, 2009, in patients discharged from the postanesthesia care unit to regular wards. For each ERT case, up to 2 controls matched for age (Ϯ10 years), sex, and type of procedure were identified. A chart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 24 publications
4
40
3
Order By: Relevance
“…Postoperative hypotension was the predominant reason for rapid response activation, and this was more common in the orthopaedic surgery group when compared to general surgery patients. This finding is similar to an American study, which found that more than 75% of RRS activations in postoperative patients occurred within the first 24 hours on the ward and that the most common reason for RRS activation was haemodynamic instability (Weingarten et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Postoperative hypotension was the predominant reason for rapid response activation, and this was more common in the orthopaedic surgery group when compared to general surgery patients. This finding is similar to an American study, which found that more than 75% of RRS activations in postoperative patients occurred within the first 24 hours on the ward and that the most common reason for RRS activation was haemodynamic instability (Weingarten et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Intraoperative emergency pages should be viewed as the equivalent of “emergency response team” activations. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Emergent page sent via the CAPS is somewhat analogous to healthcare team members initiating rapid response team calls for hospitalized patients. 9 …”
Section: Discussionmentioning
confidence: 99%